(untitled) (Journal of Human Sciences, 2026)
This study aims to shed light on an important topic in the history of contemporary Libya: Libyan-British economic relations during the 1970s, specifically the economic relations between the two countries during the Libyan Republic era (1970-1977). This can be achieved by tracing the political and economic events that occurred throughout the period under study. Undoubtedly, economic relations between countries undergo phases of fluctuation and change, sometimes strengthening and sometimes weakening, depending on the economic circumstances of each country. It is also influenced by a number of factors, perhaps the most important one is the political factor, as politics and economics influence each other. Therefore, this study attempts to Investigates the nature of economic relations between the two countries during the period in question, the changes that occurred, and the factors that shaped them Through British archive documents.